The Art of organizing anything : simple principles for organizing your home, your office, and your life. - Maggio, Rosalie. 4 0 16; 5 (New York : McGraw-Hill, 2009)
Offers advice for de-cluttering one's home or workplace, thereby reducing stress and becoming more efficient.
Includes index.
Keywords: 2 -- 0; 6; Psychological aspects.;Psychological aspects. -- Storage in the home.;Orderliness.;Organization;Storage in the home.;Orderliness.;Management; 20; 2